Three-Phase Freak Waves - Smirnov, A.O.; Matveenko, S.G.; Semenov, S.K.; Semenova, E.G. (Symmetry, Integrability and Geometry: Methods and Applications, 2015)
In the article, we describe three-phase finite-gap solutions of the focusing nonlinear Schrödinger equation and Kadomtsev-Petviashvili and Hirota equations that exhibit the behavior of almost-periodic ''freak waves''. We also study the dependency of the solution parameters on the spectral curves.